Chemical modification of silica gel surface with a carbothioamide Schiff base for removal of Cr(III) ions from wastewater samples - Cimen, Aysel; Bilgic, Ali; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Elsevier Science Inc, 2020)
In this study, a low-cost adsorbent was synthesized to efficiently remove Cr(III) ions from aqueous solutions and wastewater. First, 3-chloropropyl-trimethoxy silane (CPTS) was modified on silica gel (Si). Then, (E) -2- (1-(3-methyl-3-phenyl cyclobutyl)-2-morpholino ethylidene) hydrazine carbothioamide (PMH) Schiff base was immobilized on the Si-CPTS compound, and the Si-CPTS-PMH adsorbent was synthesized. The newly synthesized adsorbent was characterized through using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy. Several experiments using batch method were conducted to investigate the maximum adsorption capacity of Cr(III) ions on Si-CPTS-PMH adsorbent. The effect of several factors including pH, contact time and amount of adsorbent, temperature and concentration on the adsorption of Cr(III) ions were investigated. To illuminate the adsorption mechanism, Langmuir, Freundlich and Dubinin-Radushkevich (D-R) adsorption isotherms and thermodynamic calculations (Delta G degrees, Delta S degrees and Delta H degrees) were used. The optimum values obtained from this study were 6, 150 min, 0.025 g, 20 mg/L and 323.15 K for pH, interaction time, adsorbent amount, concentration and temperature, respectively. As a result, the newly synthesized support material can be used for the removal of Cr(III) ions both in industrial wastewater and aqueous solutions.
Keywords: Adsorption; Chromium; Surface treatments; Functional adsorbent material; Silica gel; Immobilization